Improving smile and dental esthetics: A comprehensive periodontal and restorative approach after orthodontics - Chaves, Eros; Rodriguez, Juan; Peres, Maria F. S.; Cunningham, Geoffrey (European Journal of General Dentistry, 2014)
The esthetic demands in smile are continually rising, being thus, critical factors such as; dental midline, smile line, incisal embrasures, tooth position, width to length crown ratio, symmetry of contra-lateral gingival margins, and gingival display need to be taken into consideration. The aim of this case report is to describe the improvement of smile esthetics in a patient that after orthodontic therapy, presented excessive gingival display, asymmetric gingival margins, and shape altered upper right and left lateral incisors, which in turn compromised dental esthetics. The present clinical case required comprehensive treatment process, including proper diagnosis and excellent communication between the prosthodontist and periodontist in order to carry out successful esthetic crown lengthening and restorative dentistry. Results were followed-up for 2 years after the case completion. A pleasant smile was obtained, showing stability over time.
Keywords: Excessive gingival display; gingival margins; periodontal surgery; prosthodontics; smiling